Biodegradation of polymeric material and adhesive properties of cells of microorganisms - Zaikov, Gennady; Gumargalieva, Klara; Artsis, Marina (Publishing House of Lviv Polytechnic National University, 2010)
The chemical composition of cell membranes of microscopic fungi destroying polymericmaterials is analyzed. The concentrations of the major chemical components –phospholipids, glycans, and amines – in nine types of fungi are estimated. The measured ratios of these components provide an estimate of the hydrophobic properties of conidia, controlling microorganism adhesion to polymer surface and subsequent degradation of polymeric materials. Проаналізовано хімічну структуру клітинних мембран мікроскопічних грибків, що руйнують полімерні матеріали. Для дев’ятьох типів грибків встановлені концентрації основних хімічних компонентів – фосфоліпідів, глісанів і амінів. Одержані дані дозволяють оцінити гідрофобні властивості конідії, що дає можливість контролювати її адгезію до полімерних поверхонь та подальшу деградацію полімерних матеріалів.
Біодеградація полімерних матаріалів і адгезійні властивості клітин мікроорганізмів
Keywords: biodegradation; polymer; materials; adhesive; properties; cells; microorganisms; біодеградація; полімер; матеріали; адгезія; властивості; клітини; мікроорганізми